Globalisation, Christian churches and ecumenism - Gheorghiu, Christian (Trinity College (Dublin, Ireland). Department of Sociology, 2007)
This dissertation offers an exploration into the multidimensional processes of globalisation in conjunction with the ecumenical movement. It investigates how combinations of ecumenical events and practices reveal various global meanings when investigated through the methods of historical sociology.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin